FEEDING STRATEGY Drosophila melanogaster TERHADAP EKSTRAK Averhoa carambolla - Sari, Rona Taula (Universitas Tanjungpura, 2016)
Feeding strategy Drosophila melanogaster can be to know from type of food is digested and other aspects of relationship with nutrients needed of body. Feeding strategy Drosophila melanogaster can be observed of exstract Averhoa carambolla foul, cook and young. The results of investigation showed feeding strategy Drosophila melanogaster pattern extract Averhoa carambolla foul, cook and young done by gathering with persentage like of foul 20 %, cook 30%, and young 70%. Keyword: Feeding strategy, Drosophila melanogaster, and Averhoa carambolla.